Effects of Stigma and Discrimination Reduction Trainings Conducted Under the California Mental Health Services Authority An Evaluation of NAMI's Ending the Silence - Wong, Eunice C. (RAND Corporation, 2015)
This paper evaluates the short-term outcomes of students attending the National Alliance on Mental Illness' Ending the Silence presentations, delivered across three high schools in a Northern California school district.